2023
DOI: 10.1002/glia.24371
|View full text |Cite
|
Sign up to set email alerts
|

Microglia directly associate with pericytes in the central nervous system

Abstract: Cerebral blood flow (CBF) is important for the maintenance of brain function and its dysregulation has been implicated in Alzheimer's disease (AD). Microglia associations with capillaries suggest they may play a role in the regulation of CBF or the bloodbrain-barrier (BBB). We explored the relationship between microglia and pericytes, a vessel-resident cell type that has a major role in the control of CBF and maintenance of the BBB, discovering a spatially distinct subset of microglia that closely associate wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
3
13
0
Order By: Relevance
“…Consistent with our previous report (Morris et al, 2023a), only ~7% of OPCs were labelled with DsRed across all brain regions analysed (Supplementary Figure 3A-C). OPCs that were DsRed + also had a significantly less intense nuclear DsRed signal compared to pericytes (Supplementary Figure 3D; p < 0.0001).…”
Section: Tamoxifen Administration Induces Pericyte Ablation In Transg...supporting
confidence: 92%
“…Consistent with our previous report (Morris et al, 2023a), only ~7% of OPCs were labelled with DsRed across all brain regions analysed (Supplementary Figure 3A-C). OPCs that were DsRed + also had a significantly less intense nuclear DsRed signal compared to pericytes (Supplementary Figure 3D; p < 0.0001).…”
Section: Tamoxifen Administration Induces Pericyte Ablation In Transg...supporting
confidence: 92%
“…A recent study discovered that microglia directly associate with pericytes(Morris et al 2023). Utilizing the MICrONS dataset, the authors suggested a direct contact between microglial and pericyte cell bodies through an astrocytic endfoot fenestration.…”
Section: Discussionmentioning
confidence: 99%
“…The recent literature data point to a close association and interaction between brain vasculature and microglia. Indeed, under steady-state conditions, 20%-30% of microglia in the adult brain are associated with blood vessels (Bisht et al, Mondo et al, 2020), and their processes are in close contact with different components of the neurovascular unit, including endothelial cells, pericytes and astrocytes (Császár et al, 2022;Morris et al, 2023). Interactions between microglial processes and vascular structures are important for the maintenance of optimal capillary diameter and cerebrovascular blood flow under basal conditions as well as during sensory stimulation-induced functional hyperemia, and the absence of microglia or blockade of microglial P2Y 12 receptors substantially impairs neurovascular coupling (Bisht et al, 2021;Császár et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of inflammation and before any detectable change in permeability of the blood-brain barrier, this migration toward and accumulation around cerebral vessels likely served to protect blood-brain barrier integrity (Haruwaka et al, 2019). This integrity seems to be impaired in post-mortem AD brain tissue with microglia showing a reduced association with capillaries and pericytes, which might contribute to vascular pathology (Morris et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation